Acute toxicity of diazinon 60EC to freshwater snakehead Channa punctatus (Block, 1793) - Akter, Reshma; Ahmed, Md Kawser; Mollah, Md Abdur Rob; Islam, Md Monirul; Hasan, Mehedi Mahmudul (Bangladesh Journal of Zoology, 2009)
Bangladesh J. Zool. 35(2): 381-389, 2007